Cardiopulmonary resuscitation education program - PERC - Guerra Lucena Matias Alencar, Lara; de Sousa Soares, Douglas; Castro Gurgel Lopes, Priscilla; Leal Chagas Fernandes, Virna; Roberto Martins Rodrigues Sobrinho, Carlos Roberto (Guará Journal, 2025)
Cardiopulmonary arrest, a complication of cardiovascular disease, is the leading cause of death worldwide. Considering the importance of disseminating and updating knowledge on this topic, the PERC (Cardiopulmonary Resuscitation Education Program) was created with the goal of training laypeople, academics, and healthcare professionals on the appropriate actions when responding to a cardiac arrest victim through theoretical and practical classes. Since 1996, more than 8,000 people have been directly trained by the Program, which follows the guidelines of the American Heart Association (AHA), aiming to reduce the number of disabilities in this still prevalent issue in the state of Ceará.
Keywords: Cardiopulmonary Arrest; Cardiopulmonary Resuscitation; Training